The Influence of Bee Venom Melittin on the Functioning of the Immune System and the Contractile Activity of the Insect Heart—A Preliminary Study - Jan Lubawy; Arkadiusz Urbański; Lucyna Mrówczyńska; Eliza Matuszewska; Agata Światły-Błaszkiewicz; Jan Matysiak; Grzegorz Rosiński (Toxins, 2019)
Melittin (MEL) is a basic polypeptide originally purified from honeybee venom. MEL exhibits a broad spectrum of biological activity. However, almost all studies on MEL activity have been carried out on vertebrate models or cell lines. Recently, due to cheap breeding and the possibility of extrapolating the results of the research to vertebrates, insects have been used for various bioassays and comparative physiological studies. For these reasons, it is valuable to examine the influence of melittin on insect physiology. Here, for the first time, we report the immunotropic and cardiotropic effects of melittin on the beetle Tenebrio molitor as a model insect. After melittin injection at 10−7 M and 10−3 M, the number of apoptotic cells in the haemolymph increased in a dose-dependent manner. The pro-apoptotic action of MEL was likely compensated by increasing the total number of haemocytes. However, the injection of MEL did not cause any changes in the percent of phagocytic haemocytes or in the phenoloxidase activity. In an in vitro bioassay with a semi-isolated Tenebrio heart, MEL induced a slight chronotropic-positive effect only at a higher concentration (10−4 M). Preliminary results indicated that melittin exerts pleiotropic effects on the functioning of the immune system and the endogenous contractile activity of the heart. Some of the induced responses in T. molitor resemble the reactions observed in vertebrate models. Therefore, the T. molitor beetle may be a convenient invertebrate model organism for comparative physiological studies and for the identification of new properties and mechanisms of action of melittin and related compounds.